Roma in Brekov. Family photos and historical-ethnographic text by Koloman Gunár - Cinová, Elena; Gunár, Koloman; Ort, Jan (Romano džaniben, 2024)
The contribution is a commented collection of historic photographs of Romani families living in Brekov (eastern Slovakia), compiled by Elena Cinová, a local Romani native. It is supplemented by excerpts from a previously unpublished historical-ethnographic text by her father Koloman Gunár, which he completed in 2010 and entitled História osídľovania obce Brekov Rómami (History of the Settlement of Roma in Brekov). The entire contribution enters into the discussion on the modes of writing on the Romani histories. Here, specifically, with regard to the importance of local histories recorded by the Roma themselves.